Papan Partikel Berperekat Likuida Tandan Kosong Sawit Difortifikasi dengan Fenol Formaldehida (Particleboard Bonded with Phenol Formaldehyde-Fortified Oil Palm Empty Fruit Bunch Liquid ) - Adesna Fatrawana; Surdiding Ruhendi; Sena Maulana; Deded S Nawawi; Fauzi Febrianto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2016)
Lignocellulosic waste from oil palm industry is a potential versatile resource. It can be used as raw material of bio-composite, pulp and paper, bioenergy, and many chemicals products.  The aimed of this research was to investigate the characteristics of particleboard from oil palm empty fruit bunch (EFB) bonded with phenol formaldehyde (PF)-fortified oil palm EFB liquid adhesive.  Fortification level of EFB liquid was varied at 5, 10, and 15%. The adhesive level of 10, 15, and 20% were used for particleboard manufactures with target density of 0.7 g cm-3. The particleboard quality was evaluated based on its physical (density, moisture content, thickness swelling) and mechanical properties (modulus of elasticity, modulus of rupture, internal bonding, and screw holding resistant) according to JIS standard. In order to improve bonding quality, the EFB particles was treated by hot water at 100 oC for 6 h.  The results showed that the quality of particleboard increased by addition of fortifier as well as adhesive level, except for thickness swelling. The best particleboard properties was produced with 20% adhesive level and 15% fortifier, however, physical and mechanical properties of most particleboard produced did not satisfy the JIS A 5908:2003 requirement.Keywords: empty fruit bunch, fortifier, liquid adhesive, oil palm, particleboard, phenol formaldehyde